Detection of Hybrids in Willows (Salix, Salicaceae) Using Genome-Wide DArTseq Markers - Radim J. Vašut; Markéta Pospíšková; Jan Lukavský; Jan Weger (Plants, 2024)
The genus Salix, comprising some 400–500 species, is important in various alluvial or wet habitats of the northern hemisphere. It is a promising crop for applications such as biomass production, biofuels, or environmental projects. Clear species delimitation is crucial in ecology, biotechnology, and horticulture. DArTseq markers, a genome-wide technique, were tested for species and hybrid identification. A total of 179 willow samples were analysed, including six species of Salix subgen. Salix and four species of Salix subgen. Vetrix, including those used in biomass crop production, representing important European taxa. Identification of species-specific markers, clustering analyses (principal coordinate analysis, neighbor-joining) and Bayesian methods (Structure) unambiguously identified putative hybrids. In addition to demonstrating the high efficiency of DArT-seq markers in identifying willow hybrids, we also opened-up new questions about hybridisation processes and systematics. We detected unidirectional hybridisation between S. alba and S. fragilis, forming backcross hybrids, and we rejected the hypothesis that S. fragilis does not occur naturally in Europe. Further, the isolated position of Salix triandra within the genus was confirmed.